Pengaruh Live Streaming, Affiliate Marketing, dan Online Customer Review terhadap Keputusan Pembelian pada Marketplace Shopee (Studi pada Mahasiswa di Condong Catur) - Lamik, Yosias Umbu; Dwiyanto, Bambang Sugeng (Universitas Proklamasi 45, 2025)
This study aims to examine the influence of live streaming, affiliate marketing, and online customer reviews on purchase decisions on the Shopee marketplace. The research employs a quantitative approach with an associative research design. The sample consists of 100 university students residing in Condong Catur who have previously made purchases on Shopee. Data were collected using a Likert-scale questionnaire and analyzed using the Partial Least Squares (PLS) method through SmartPLS 4.0. The results indicate that live streaming and online customer reviews have a positive and significant influence on purchase decisions, while affiliate marketing has no significant effect.